Edital PRGO nº 15, de 28 de agosto de 2017 - Mariane Guimaraes de Mello Oliveira; Otavio Balestra Neto; Viviane Vieira de Araujo (DMPF-e, Brasília, DF, 30 ago. 2017. Caderno Administrativo, p. 33., 2017)
Dispõe sobre a eleição do procurador regional Eleitoral e de seu substituto.